BTC1.06 Calmodulin(CaM) as a potential cancer prognostic marker promotes cell invasion and migration, associated with the induction of EMT in Glioblastoma. (19th September 2018) - Yuan, F; Yang, X
Abstract: Background: Numerous studies have shown that calmodulin (CaM) is considered to be the major regulator of Ca2+-dependent signaling, which involves the regulation of cell proliferation, programmed cell death and autophagy in cancer. However, little is known about underlying mechanism of CaM in glioblastoma multiforme (GBM) invasion and migration. Material and Methods: Calmodulin (CaM) expression levels were examined in glioma tissues and normal brain (NB) tissues. The molecular mechanisms of calmodulin expression and its effects on cell invasion, migration and associated with the induction of EMT were also explored by Western blot, Immunofluorescence staining, Transwell chamber assay and Wound healing assay as well as in vivo tumorigenesis in nude mice. Results: Compared with normal tissue and lower grade glioma (LGG) specimens, CaM expression level was elevated in GBM specimens. Knocking down CaM expression could significantly decreased glioma cell migration and invasion abilities in vitro and in vivo. Simultaneously, knockdown of CaM resulted in restoration of E-cadherin expression and suppression of mesenchymal cell markers, such as Vimentin, ZEB1 and N-Cadherin. which indicted that CaM promoted EMT-like process in glioma in vitro. Conclusion: These findings suggested that CaM maybe provides novel therapeutic strategy targeting the invasive of GBM.